2021
DOI: 10.1038/s41598-020-80708-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the interactions of poly(methyl methacrylate) and poly(vinyl chloride) nanoparticles with BHK-21 cell line

Abstract: Microplastic and nanoplastic particles are prevalent in the environment and are beginning to enter the living system through multiple channels. Currently, little is known about the impact of plastic nanoparticles in living organisms. In order to investigate the health impact of micro- and nanoparticles of common polymers in a systematic way, luminescent plastic nanoparticles from two common polymers, polyvinyl chloride (PVC) and poly (methyl methacrylate) (PMMA) with relatively narrow size distribution are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…Microplastics can impact cells and organisms directly and indirectly, physically and chemically, and via an array of harmful effects, including irritation, oxidative damage, impairment of digestion, genotoxicity, metabolic changes, chemical leaching, and fluctuations of the microbiome (Deng et al 2017 ; Ibrahim et al 2021 ; Jin et al 2019 ; Kumar et al 2020 ). As microplastics age and weather in the environment, their properties such as size, shape, surface charges, and surface-bound groups can change, significantly altering the mechanisms with which they interact with cells and tissues, including the ability to be endocytosed (Brachner et al 2020 ; Mahadevan and Valiyaveettil 2021 ; Ramsperger et al 2020 ; Zarus et al 2021 ). For this study we used virgin, pristine microspheres of PS and PE to decrease the size range and to avoid the variables of different shapes, surface charges and groups, as well as foreign chemicals absorbed from the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics can impact cells and organisms directly and indirectly, physically and chemically, and via an array of harmful effects, including irritation, oxidative damage, impairment of digestion, genotoxicity, metabolic changes, chemical leaching, and fluctuations of the microbiome (Deng et al 2017 ; Ibrahim et al 2021 ; Jin et al 2019 ; Kumar et al 2020 ). As microplastics age and weather in the environment, their properties such as size, shape, surface charges, and surface-bound groups can change, significantly altering the mechanisms with which they interact with cells and tissues, including the ability to be endocytosed (Brachner et al 2020 ; Mahadevan and Valiyaveettil 2021 ; Ramsperger et al 2020 ; Zarus et al 2021 ). For this study we used virgin, pristine microspheres of PS and PE to decrease the size range and to avoid the variables of different shapes, surface charges and groups, as well as foreign chemicals absorbed from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although both the PE and the PS were supplied as microspheres of the pure polymers, presumably without plasticizers or copolymers, the leaching of trace amounts of monomers or catalysts used in the manufacture each plastic type cannot be ruled out. The size of the microspheres used in this study was also 1 μm or greater, decreasing the possibility of their endocytosis (Mahadevan and Valiyaveettil 2021 ), although the measurement of this property was beyond the scope of this study. Thus, the most likely mechanisms by which the microplastics impacted the cells used in this study were physical interactions with the cells and their adjacent in vitro environments.…”
Section: Discussionmentioning
confidence: 99%
“…Although preparation of nanoscale particles by precipitation has been thoroughly studied in the case of biodegradable polymers for medical use, [17,18] there have been few studies of the preparation of other polymers. Precipitation has been used to produce nanoparticles of polyolefins [19][20][21] and PVC; [22] however, the resulting particles have an extremely low molecular weight, [19] are heterogeneous in shape, [20] or are contaminated with surfactant. [21,22] Precipitation has also been used to produce PS nanoparticles; [23] however, this approach used tetrahydrofuran, which was oxidized to toxic, nonvolatile peroxides, [24] and the use of antioxidants to address this issue (e.g., 2,6-ditert-butyl-p-cresol) resulted in contamination of the particles because of their low volatility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nano and micro-scale surface topographies can affect cell proliferation, and it was shown that the proliferation rate increased on microstructures possibly due to the increasing number of attachment sites on micropatterned surfaces [75][76][77]. However, decreased metabolic activity could result from the nature of PMMA itself, which is known to arrest cells at the stationary (G0/G1) phase of the cell cycle [78,79]. Moreover, it was also reported that deformations in the nuclei of the cells led to the senescence of the cells especially when the nuclear abnormalities were originated from Lamin A/C-related genes and proteins [80].…”
Section: Testing the Metabolic Activity And Proliferation Of Cells On...mentioning
confidence: 99%